Survey of Keyword Adjustment of Published Articles Medical Subject Headings in Journal of Mazandaran University of Medical Sciences (2009-2010) - Kabirzadeh, Azar (AVICENA, d.o.o., Sarajevo, 2013)
CONFLICT OF INTEREST: NONE DECLARED INTRODUCTION: Keywords are the most important tools for Information retrieval. They are usually used for retrieval of articles based on contents of information reserved from printed and electronic resources. Retrieval of appropriate keywords from Medical Subject Headings (MeSH) can impact with exact, correctness and short time on information retrieval. Regarding the above mentioned matters, this study was done to compare the Latin keywords was in the articles published in the Journal of Mazandaran University of Medical Sciences. METHOD: This is a descriptive study. The data were extracted from the key words of Englsih abstracts of articles published in the years 2009–2010 in the Journal of Mazandaran University of Medical Sciences by census method. Checklist of data collection is designed, based on research objectives and literature review which has face validity. Compliance rate in this study was to determine if the keywords cited in this article as a full subject of the main subject headings in a MeSH (Bold and the selected word) is a perfect adjustment. If keywords were cited in the article but the main heading is not discussed in the following main topics to be discussed with reference to See and See related it has considered has partial adjustment. RESULTS: Out of 148 articles published in 12 issues in proposed time of studying, 72 research papers were analyzed. The average numbers of authors in each article were 4 ± 1. Results showed that most of specialty papers 42 (58. 4%), belonging to the (Department of Clinical Sciences) School of Medicine, 11 (15.3%) Basic Science, 6(8.4%) Pharmacy, Nursing and Midwifery 5(6.9%), 4(5.5%) Health, paramedical Sciences 3(4.2%), and non medical article 1(1.3%) school of medicine. In general, results showed that 80 (30%) of key words have been used to complete the adjustment. Also, only 1(1.4%) had complete adjustment with all the MeSH key words and in 8 articles(11.4%) key words of had no adjustment with MeSH. CONCLUSION: The results showed that only 17 articles could be retrieved if the search words are selected from the MeSH. In this case the expected 100% of published articles titles at this university the validity of exchange of research projects which is something noteworthy. The lack of correlation between number of authors and matching of Keywords with MeSH, may mean all of the papers’ authors did not take part in writing and it is understanding that only one author wrote the paper.